Quantification of biofilm thickness using a swept source based optical coherence tomography system - Meleppat, Ratheesh Kumar (2018)
Optical coherence tomography (OCT) is a non-invasive, non-contact optical measurement and imaging technique that relies on low coherence interferometry. Apart from bio-imaging applications, the applicability of OCT can be extended to metrological investigations because of the inherent capability of optical interferometry to perform precise measurement with high sensitivity. In this paper, we demonstrate the feasibility of OCT for the measurement of the refractive index and thickness of bacterial biofilm structures grown in a flow cell. In OCT, the depth profiles are constructed by measuring the magnitude and time delay of back reflected light from the scattering sites by means of optical interferometry. The optical distance between scattering points can be obtained by measuring the separation between the point spread functions (PSF) at the respective points in the A-scan data. The refractive index of the biofilm is calculated by measuring the apparent shift in the position of the PSF corresponding to a reference surface, caused by the biofilm growth. In our experiment, the base layer of the flow cell is used as the reference surface. It is observed that the calculated refractive index of the biofilm is close to that of water, and agrees well with the previously reported value. Finally, the physical thickness of the biofilm is calculated by dividing the optical path length by the calculated value of refractive index.